RISK FACTORS OF DEVELOPMENT OF PLANTATSIONNY AFFORESTATION - Elena Kolesnichenko; Ivan Torzhkov; Yana Radyukova; Svetlana Morkovina (Вестник Северо-Кавказского федерального университета, 2022)
This article is about relation to the business sector functioning in the forest sphere an urgent task the choice of adequate forms of business on the basis of forecasting and the accounting of influence risky. The purpose of this article is development of organizational and methodical tools of an assessment and the accounting of risk factors at the choice of a type offorest business on the basis of afforestation. In article risk factors of activity of structures offorest business in the sphere offorest afforestation (the fires and reproduction of insects wreckers) are allocated and the technique of an assessment of losses on restoration of a plantation at various options of probability of approach of these risk events for mini- is offered, to a midi- and maxirotational plantations. According to the offered algorithm, the author has carried out an assessment ofprobability of approach of risk events and opportunities of obtaining the maximum profitability for different types ofplantations with various density of landing.